2016
DOI: 10.1002/wps.20318
|View full text |Cite
|
Sign up to set email alerts
|

The CHANGE trial: no superiority of lifestyle coaching plus care coordination plus treatment as usual compared to treatment as usual alone in reducing risk of cardiovascular disease in adults with schizophrenia spectrum disorders and abdominal obesity

Abstract: Life expectancy in patients with schizophrenia is reduced by 20 years for men and 15 years for women compared to the general population. About 60% of the excess mortality is due to physical illnesses, with cardiovascular disease being dominant. CHANGE was a randomized, parallel‐group, superiority, multi‐centre trial with blinded outcome assessment, testing the efficacy of an intervention aimed to improve cardiovascular risk profile and hereby potentially reduce mortality. A total of 428 patients with schizophr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
146
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(162 citation statements)
references
References 56 publications
8
146
2
Order By: Relevance
“…As shown in Tables and , 38 studies met criteria for inclusion in the qualitative synthesis and all were published after 2005 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Tables and , 38 studies met criteria for inclusion in the qualitative synthesis and all were published after 2005 .…”
Section: Resultsmentioning
confidence: 99%
“…Sample sizes varied largely in relation to the type of study; for instance, the cohorts included between 2682 and 1.1 million participants and were >80% male . By contrast, the cross‐sectional studies included a total of 2698 cases (across Stages 1–4) and 3129 HC and all except one of these studies comprised 55–100% males. The median sample age was about 33 years, and 13 studies reported the inclusion of affective or schizoaffective alongside non‐affective psychoses .…”
Section: Resultsmentioning
confidence: 99%
“…In the very recent 3-arm CHANGE trial, one of the largest, longest, and most ambitious RCTs in the field to date, Speyer et al 18 randomized 428 patients with schizophrenia spectrum disorders and abdominal obesity to receive lifestyle training with care coordination and treatment as usual, care coordination with treatment as usual, or only treatment as usual.…”
Section: The Change Trialmentioning
confidence: 99%
“…An important strength of this adequately powered study 18 is that it was pragmatic; there were few exclusion criteria, and there were no elements in the treatment program that were mandatory and that might have resulted in the elimination of more severely ill patients. Thus, the trial had good external validity.…”
Section: Table 1 Outcome Of Exercise Intervention As a Sole Behaviormentioning
confidence: 99%
See 1 more Smart Citation